Building the resilience of agri-food systems to compounding shocks and stresses: A case study from Melbourne, Australia - Murphy, Maureen; Carey, Rachel; Alexandra, Leila (Frontiers in Sustainable Food Systems, 2023)
The war in Ukraine is causing significant disruption to global agri-food systems, , which are still recovering from the effects of the COVID-19 pandemic. In Australia, these global shocks followed a series of localized climate-induced crises from forest fires, floods and drought. There is a pressing need to increase our understanding of ways to strengthen the resilience of agri-food systems to multiple shocks and stresses that co-occur or follow on each other. The aims of this study in Melbourne, Australia, were to investigate how forest fire and pandemic shocks affected the agri-food system, to identify vulnerabilities in the system, and to explore opportunities to build resilience to future shocks and stresses. Semi-structured interviews were conducted during 2020-21 with 41 key stakeholders from government, industry and civil society organizations. Vulnerabilities identified in agri-food supply chains included geographic and corporate concentration, complex ‘just in time’ supply chains, critical infrastructure and logistics, and workforce availability. Strategies identified to build the resilience of agri-food systems include increasing the diversity of supply chains, decentralization, collaboration throughout agri-food supply chains, and ensuring sustainable livelihoods. Our study highlights the cascading effects of multiple shocks and stresses on agri-food systems, and the need for greater policy focus on transformative actions that build the resilience of agri-food systems to any future shock, and that counter the cumulative effects of underlying environmental stresses.